THE BASIC TERMS OF ARCHITECTURAL GRAPHICS: ARTISTIC ASPECT - МИХАЙЛОВА , Р. Д.; Перепелиця, О. В. (Art and Design, 2022)
The purpose of the article is to study the art history terminology of architectural graphics as a full-fledged part of the multifaceted phenomenon of graphic culture, where the conceptual and terminological apparatus of architectural graphics is considered in the context of the artistic value of graphic works as the result of a historically objective specific type of creative activity of an architect-artist and architect-designer. Methodology. This study includes general scientific methods – empirical (observation and description), theoretical (analysis and synthesis, abstraction and generalization, induction and deduction), art history, historical-evolutionary, comparative, systemic, functional analysis, as well as summation and explanation. Results. The concept of a range of basic terms in architectural graphics is formed on a historical and evolutionary basis, which explains their dual nature, due to the historical conditions of the development of this practice – engineering and construction (technical) and artistic (figurative). To understand the essence of the main terms, including the concept of "architectural graphics", the work includes a historical and historical excursion, which forms an idea of its appearance, formation, theoretical and semantic content at different historical stages. A modern model of the relationship between the technical and artistic foundations of architectural graphics is proposed, a range of basic terms of architectural graphics is highlighted and their content is revealed from the point of view of art history, their explanation and formulation are given. The scientific novelty of the work lies in the appeal in the study of architectural graphics to the artistic and visual aspects, in identifying certain contradictions in the interpretation of the meaning of the main terms of architectural graphics in the context of oppositions of architectural and construction, engineering and technical and art history approaches. Practical significance. Scientific comprehension of the basic concepts of architectural graphics, which is a toolkit of project practice, is essential for the practical creative activity of modern architects a designers.